(untitled) (Nonconventional Technologies Review, 2022)
The innovative method of geopolymer concrete making by completely replacing the cement with coal fly ash and granulated blast furnace slag (residual aluminosilicate materials) was experimentally applied and presented in the paper. Compared to other experiments described in literature, the work originality is the significant increasing of slag ratio (15-25 %) in the aluminosilicate binder, to increase the compressive strength despite the decrease in workability. Sodium silicate and aqueous solution of sodium hydroxide were used as activators. River sand (fine aggregate) and natural gravel (coarse aggregate) completed the concrete making recipe. The compressive strength had increasing values (above 51 MPa) with the increase of slag ratio, density decreased up to 2290 kg/m3, fresh concrete workability according to standard for concrete slump test decreased from 70 mm up to 45 mm, while water absorption was relatively constant between 0.78-0.80 vol. %. The making variant adopted as optimal was that with 80 % fly ash and 20 % slag having the compressive strength of 53.3 MPa, density of 2298 kg/m3 and fresh concrete workability of 58 mm (i.e. a medium workability).